Upaya Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Matematika di SDN Banjar Agung 2 - Anita, Anita; Aprilia, Deya; Rahman, Patra Aghtiar (ARZUSIN, 2024)
This study was motivated by the lack of motivation in students, especially in learning mathematics. From the results of observations and interviews, students' interest in learning is very high by using creative and innovative learning media, so researchers use snakes and ladders learning media to increase student learning motivation, especially in learning math. The purpose of this study was to increase student learning motivation by using snakes and ladders learning media in the concept of multiplication in mathematics learning. This research method uses a qualitative descriptive method. Qualitative descriptive research methods are carried out to describe and provide an overview of phenomena carried out by humans who pay more attention to characteristics and quality. This research was conducted at SDN Banjar Agung 2 on all 3rd grade students totaling 37 students. Data validity in this study using source triangulation, technique triangulation and time triangulation. Data collection techniques use observation, interviews and documentation. Based on the results of the study, it shows that creative and innovative learning media can increase student motivation in participating in math learning.